Refleksi Filsafat Idealisme - Beliani, Karespa (Journal of Innovation in Teaching and Instructional Media, 2024)
Idealism greatly contributes to the world of education, or the progress of the world of education. We can see it in terms of methods and curriculum in schools today. This article provides us with information in the form of a review of idealism in the study of philosophy, both in the areas of understanding religion, economics, politics and education. The writing method is carried out by article review. Idealism is a philosophical school which believes that everything exists at the level of ideas, this is the result we get. Real reality primarily exists in the reality of ideas and thoughts, not in material things. However, idealism itself does not deny the existence of matter. Matter is the outermost part of the deepest essence which is called reason or spirit, so matter is the outer shell of essence, spirit, reason or spirit, values. Therefore, idealism often uses concepts that involve abstractions such as thought, reason, values, and character. Idealism assumes that the properties of objects are spiritual, immaterial, and idealistic.